Pengembangan Sistem Piconet Pervasive pada Transmisi Data Rate Video Streaming Melalui Bluetooth - Andi Hasad; Abdul Hafid Paronda (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
The purpose of this research is to develop Piconet Pervasive system from previous research that analyzed security system and optimized system performance of video streaming rate data transmission over Bluetooth Piconet Pervasive network, using Symbian OS on the client side. This research was still running on client side Symbian platform by using point-topoint topology. Based on previous research, in this study, Piconet pervasive system is developed. The system runs on Android and Symbian operating system on the client side, using point-tomultipoint topology. This research is a quantitative research with experimental method. Data analysis is carried out using descriptive statistics method. In this paper, a piconet pervasive system that meets Cisco standard from previous research is developed, by optimizing server-side and Bluetooth device on client-side, where the result of packet loss meets Cisco standard. All average values of throughput, delay, jitter, and packet loss parameters are eligible for Cisco standard video streaming for 5 m and 10 m measurements, where packet loss is below 5%. The results show that the greater the interference of Wi-Fi on the Bluetooth Piconet Pervasive network, the quality of video received by the client (mobile phone) decreases, marked by the increasing value of average packet loss obtained during the video streaming.